Formação e qualificação dos profissionais de saúde: fatores associados à qualidade dos serviços de atenção primária à saúde - Oliveira, Mariana Policena Rosa de (2014)
Advances in educational and health sectors in the twentieth century have influenced the concepts and practices of health professionals, particularly in primary health care, emphasizing the importance of training and qualification for the improvement of health care based on realities and needs of the population. The present research aimed to examine the profile of training and qualification of the professionals of the Family Health Strategy (FHS) and factors associated with quality of Primary Health Care (PHC) services in the northwest Goiania. This is a cross-sectional study whose data were collected through a structured interview, including the application of the Primary Care Assessment Tool - PCA-Tool. The study included 48 doctors and 44 nurses from FHS teamwork. Data were analyzed using the U -test of Man-Whitney, chi-square or Fischer test, Student-t test and Poisson regression, with 5% significant level. The results showed significant differences (p <0.05) between the profile of training and qualifications of doctors and nurses. Doctors had higher turnover rates while nurses were the most experienced and trained as well as had a greater bond with the FHS. The evaluation of the PHC attributes indicated a low essential score (6.5) and a high non essential score (96.9), totalizing a high general PHC score (6.7). The analysis of the professional profiles associated with the quality of PHC services pointed out that the low turnover rates of doctors and the positive contribution of trainings for professional development were associated with better quality of services. However, this association did not remain in the final explanatory model. It is concluded that nurses have a professional profile more conducive to working on PHC and the training and skills of health professionals in the northwestern region of Goiânia are related to the quality of PHC.